2017
DOI: 10.3390/ani7050039
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Profiles of Brown and Sloth Bears in Captivity

Abstract: Simple SummaryAnimal personality research is a growing field, since understanding animal personalities has notable implications in ecology and the evolution of animal behaviours. In the current study, we tested different methods described in the literature to obtain robust individual behavioural profiles. Data collected through behavioral observations were categorised into activity budgets, space usage, and social interactions for each individual. In addition, behavioural profile questionnaires were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
(88 reference statements)
4
19
0
Order By: Relevance
“…The methodology for these questionnaires was adapted from Chadwick's research on cheetah personality, as previously described [6,31]. Questionnaires listed 31 traits, which were rated on a scale of 1 (trait was never exhibited) to 12 (trait was always exhibited) by the keepers for each tiger.…”
Section: Personality Profilesmentioning
confidence: 99%
“…The methodology for these questionnaires was adapted from Chadwick's research on cheetah personality, as previously described [6,31]. Questionnaires listed 31 traits, which were rated on a scale of 1 (trait was never exhibited) to 12 (trait was always exhibited) by the keepers for each tiger.…”
Section: Personality Profilesmentioning
confidence: 99%
“…The results obtained in the present study have shown that the keepers knew every penguin very well, and they were able to consistently evaluate their behavioral characteristics [23,24]. This data is useful to underline the importance of the professional figure of the zookeeper, which has prominent responsibilities in the daily welfare of the animals [29,38].…”
Section: Discussionmentioning
confidence: 52%
“…Observer ratings have been used in assessing the welfare and personality of farm animals [32] and the personality of companion animals [33]. In the same way, keeper ratings can be used to investigate the welfare and personality of zoo animals [23,34]. A fundamental condition in personality studies is that the assessment of personality traits must be both reliable and valid [25,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2001 review, Gosling identified 187 studies in 64 species, which included mammals, birds, and fish, as well as reptiles, amphibians, arthropods, and mollusks. Perhaps unsurprisingly, animal personality research has focused largely on mammals, ranging from the African striped mouse ( Rhabdomys dilectus , Joshi and Pillay, 2016) to brown and sloth bears ( Ursus arctos arctos and Melursus ursinus inornatus , respectively, Pastorino et al, 2017), snow leopards ( Uncia uncia , Gartner and Powell, 2012), African elephants ( Loxodonta africana , Horback et al, 2013) and a number of non-human primate species including chimpanzees (Freeman et al, 2013), rhesus macaques ( Macaca mulatta , Capitanio, 1999), and squirrel monkeys ( Saimiri sciureus , Polgár et al, 2017). Although fewer studies have been devoted to other taxa, some work has been conducted with a variety of reptile species, including snakes, lizards, and turtles.…”
Section: Introductionmentioning
confidence: 99%